Recent advances in environmental economics - List, John A., 1968-; Zeeuw, Aart de, 1952-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2002)
In this book, distinguished scholars from Europe and the US examine a range of topical issues in environmental and resource economics. Employing cutting-edge tools, they take a fresh look at some of the most significant international and domestic issues at the forefront of public policy debates.
1. A reconsideration of environmental federalism / Wallace E. Oates -- 2. Global environmental governance, political lobbying and transboundary pollution / Surjinder Johal and Alistair Ulph -- 3. Endogenous transfrontier pollution / Michael Rauscher -- 4. Allocating greenhouse gas emissions among countries with mobile populations / Michael Hoel -- 5. Environmental regulation and international trade : a general equilibrium approach / Chris Elbers and Cees Withagen -- 6. The ups and downs of the environmental Kuznets curve / Arik Levinson -- 7. Participation in industry-wide voluntary approaches : short-run vs. long-run equilibrium / Na Li Dawson and Kathleen Segerson -- 8. Irreversible development of a natural resource : management rules and policy issues when direct use values and environmental values are uncertain / Anastasios Xepapadeas -- 9. A model of neighbourhood conditions and internal household environments / Mark Agee and Thomas Crocker -- 10. Environmental policy and the timing of drilling and production in the oil and gas industry / Mitch Kunce, Shelby Gerking and William Morgan -- 11. Using flexible scenarios in benefit estimation : an application to the cluster rule and the pulp and paper industry / Susan Kask ... [et al.] -- 12. Trade-off at the trough : TMDLs and the evolving status of US water quality policy / Carol Mansfield and V. Kerry Smith -- 13. Heterogeneous preferences and complex environmental goods : the case of ecosystem restoration / J. Walter Milon and David Scrogin -- 14. Incentives in public goods experiments : implications for the environment / Jacob Goeree -- Charles Holt and Susan Laury -- 15. An experimental test for options value : relevance for contingent valuation elicitation / David Bjornstad ... [et al.] -- 16. Is the scope test meaningful in the presence of other-regarding behaviour? / William Schulze ... [et al.].
Papers from a workshop held in Orlando, Florida, 30 November-2 December 2000.
Includes bibliographical references and index.
Keywords: Environmental economics -- Congresses; Environmental policy -- Congresses; International cooperation -- Congresses; Greenhouse gas mitigation -- Congresses; Electronic books